2012
DOI: 10.5402/2012/368520
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, Overweight, and Perceptions about Body Weight among Middle-Aged Adults in Dar es Salaam, Tanzania

Abstract: Background. Prevalence of obesity is increasing throughout the world at an alarming rate. Appropriate perception of one's own body weight is important for improved weight control behavior. This study was conducted to determine the prevalence of overweight and obesity and assess perception of body weight among middle aged adults in Dar es Salaam, Tanzania. Methods. Structured questionnaire was used to collect sociodemographic and lifestyle information including perception about body weight. Anthropometric measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
44
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 34 publications
13
44
3
Order By: Relevance
“…Over this 10 year follow-up period, the prevalence of obesity increased by 29–66% [6], while the prevalence of MetS in this same cohort at baseline was as high as 50%. Notably, 74% of the women underestimated their actual body sizes [6]; this is consistent with similar research within South Africa [7] and sub-Saharan Africa [8], confirming that African women have a greater body size tolerance, and highlighting the challenges associated with weight-loss interventions in sub-Saharan Africa.…”
Section: The Problem Of Obesity and Cardiometabolic Risk In South Afrsupporting
confidence: 80%
“…Over this 10 year follow-up period, the prevalence of obesity increased by 29–66% [6], while the prevalence of MetS in this same cohort at baseline was as high as 50%. Notably, 74% of the women underestimated their actual body sizes [6]; this is consistent with similar research within South Africa [7] and sub-Saharan Africa [8], confirming that African women have a greater body size tolerance, and highlighting the challenges associated with weight-loss interventions in sub-Saharan Africa.…”
Section: The Problem Of Obesity and Cardiometabolic Risk In South Afrsupporting
confidence: 80%
“…Research reported that Chinese girls with normal weight were more likely to misperceive themselves as overweight, whereas more Chinese boys misclassified their normal weight status as underweight [17]. The gender difference of adult Chinese American in this study was similar as Chinese adolescents and also similar as other ethnic groups [16, 18]. However, gender difference of body weight perception was not suitable for all ethnic groups.…”
Section: Discussionmentioning
confidence: 62%
“…Our previous study among middle-aged adults in Dar es Salaam also showed that a higher proportion of women perceived their weight as obese compared to men (Muhihi et al, 2012). A recent study among children and teenagers has indicated a similar pattern of more girls perceiving themselves as more overweight/obese, and consequently tend to lose weight than boys (Darshini & Rajeshi, 2013).…”
Section: Introductionmentioning
confidence: 79%